Pharmacological Management of Postpartum Haemorrhage - A. V. Rostovtsev; Yu. S. Aleksandrovich; O. V. Ryazanova; T. I. Akimenko; K. V. Pshenisnov (Вестник анестезиологии и реаниматологии, 2022)
Despite improvements in healthcare technologies, massive postpartum haemorrhage is still the leading cause of maternal morbidity and mortality worldwide. Delayed and poor-quality obstetric care can result in irreversible consequences. Well-timed assessment of blood loss, effective management of the peripartum period, and participation of multidisciplinary teams are essential to provide a specialized care. This review presents the evidence-based management of patients with the development of obstetric haemorrhage. The article presents existing contradictions in the methods of diagnosis and treatment as well as new advances in this field of medicine which require continuation of research in this direction.